Profil Suhu Pantai Peneluran Penyu Sidey: Implikasi Estimasi Jenis Kelamin Tukik Penyu - Siwom Erick Nicols Semboor; Ricardo F. Tapilatu; Vera Sabariah (Faculty of Agriculture Musamus University, 2021)
Changes in the temperature of the nesting habitat due to the impact of global warming cause damage to turtle eggs and will result in failure of hatching in turtle nests. The temperature of the turtle nesting beach on Sidey beach as a secondary nesting beach has a contribution to the existence of turtle populations in the wild. The analysis of the temperature profile of the Sidey turtle nesting beach aims to relate the temperature of the turtle nesting beach sand to hatching success, and to estimate the sex of hatchlings based on the temperature during the incubation period and the temperature of the beach sand. Temperature recording using a data logger, then analyzed using HOBOware software. The results of the analysis of the mean temperature for Sidey 1 beach of 31.75±1.70⁰C, Sidey 2 beach of 32.29±0.23⁰C, incubation temperature of nest 1 was 28.14±0.75⁰C and at nest 2 of 30.13±0.82⁰C. The mean temperature range of the Sidey beach was above the pivotal temperature for leatherback turtles for the East Pacific region, which is 29.4⁰C, while the two nest samples have a temperature mean above or below the pivotal temperature, so that the estimation of hatchling sex for Sidey beaches are female and have low hatching success.